The Moderating Effect of Financial Distress in The Relationship Between Debt Covenant And Political Cost Towards Accounting Conservatism Implementation: An Empirical Analysis From SOEs in Indonesia - Ramadhan, Allan; Ermaya, Husnah Nur Laela (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to examine the impact of debt covenants and political costs on the implementation of accounting conservatism, with financial distress as a moderation variable. Debt covenants in this study are proxied by the debt-to-assets ratio and political costs are proxied by capital intensity. In this study, financial distress as a moderating variable was measured using the Altman Z-Score Modified and accounting conservatism using an accrual measure. This study used a purposive sampling technique and resulted in a total sample of 51 companies. In this study, research data were obtained from all state-owned enterprises (SOEs) listed on the Indonesian Stock Exchange for the period 2020–2022. The analysis technique used in this research is multiple linear regression analysis with STATA v13. The findings of this study indicate that debt covenants have a significant negative effect on the implementation of accounting conservatism, while political costs do not affect accounting conservatism. Furthermore, this study proves that financial distress can moderate the effect of debt covenants on accounting conservatism. In contrast, financial distress has not shown its ability to moderate the impact of political costs on accounting conservatism. Keywords: Accounting Conservatism, Debt Covenant, Political Cost, Financial Distress